High-Intensity Interval Training Does Not Change Vaspin and Omentin and Does Not Reduce Visceral Adipose Tissue in Obese Rats - Costa, Leandro Ribeiro; Castro, Cynthia Aparecida de; Marine, Diego Adorna; Fabrizzi, Fernando; Furino, Vanessa de Oliveira; Malavazi, Iran; Anibal, Fernanda de Freitas; Duarte, Ana Cláudia Garcia de Oliveira (Frontiers in Physiology, 2021)
This study aimed to determine the expression of omentin and vaspin, inflammatory markers, body composition, and lipid profile in diet-induced obese rats and high-intensity interval training (HIIT). Forty Wistar rats were divided into four groups: untrained normal diet, trained normal diet (T-ND), untrained high-fat diet (Unt-HFD), and trained high-fat diet (T-HFD). For the animals of the Unt-HFD and T-HFD groups, a high-fat diet was offered for 4 weeks. After that, all the animals in the T-ND and T-HFD groups were submitted to HITT, three times per week, for 10 weeks (2 weeks of adaptation and 8 weeks of HIIT). Muscle (gastrocnemius), liver, epididymal adipose tissue, retroperitoneal adipose tissue, visceral adipose tissue (VAT), and serum were collected to analyze TNF-α, IL-6, PCR, IL-8, IL-10, IL-4, vaspin, and omentin. A body composition analysis was performed before adaptation to HIIT protocol and after the last exercise session using dual-energy X-ray absorptiometry. Omentin and vaspin in the VAT were quantified using Western blotting. The results showed that, when fed a high-fat diet, the animals obtained significant gains in body fat and elevated serum concentrations of vaspin and blood triglycerides. The HIIT was able to minimize body fat gain but did not reduce visceral fat despite the increase in maximum exercise capacity. Moreover, there was a reduction in the serum levels of adiponectin, IL-6, and IL-10. Finally, we concluded that, although the training protocol was able to slow down the weight gain of the animals, there was no reduction in visceral fat or an improvement in the inflammatory profile, including no changes in omentin and vaspin.